Pengaruh Kapabilitas Pemasaran, Digital Marketing Dalam Meningkatkan Kinerja Pemasaran UMKM di Kota Batu - Fadhilah, Gita Maulani; Diana, Nur; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to examine the influence of marketing capabilities and digital marketing on the marketing performance of micro, small and medium enterprises (MSMEs) in Batu City, East Java. Data was collected from 55 MSMEs using a structured questionnaire, and structural equation modeling (SEM) was used to test the research hypotheses. The research results show that marketing capability has a significant positive effect on the marketing performance of MSMEs, while digital marketing has no effect on the marketing performance of MSMEs. Furthermore, digital marketing was found not to mediate the relationship between marketing capabilities and MSME marketing performance. These findings have important implications for MSMEs in Batu City and other regions in Indonesia.. Keywords: Marketing Capabilities, Digital Marketing, Marketing Performance